Increased familiarity, knowledge and confidence with Nutrition Care Process Terminology following implementation across a statewide health‐care system. Issue 3 (7th July 2015) - Vivanti, Angela; Ferguson, Maree; Porter, Jane; O'Sullivan, Therese; Hulcombe, Julie
Abstract Aim Information on attitudes and knowledge of practising dietitians regarding the Nutrition Care Process (NCP) and International Dietetics and Nutrition Terminology (IDNT) would be useful to inform effective implementation. The present study aimed to: (i) explore dietitians' expectations, perceptions and anticipated benefits of NCP/IDNT pre and post implementation; (ii) identify perceived implementation barriers and enablers; and (iii) develop and assess a train‐the‐trainer NCP/IDNT implementation approach. Methods All Queensland Government State hospitals from metropolitan, regional and remote areas were included in the study. Dietitian champions (n = 17) attended one face‐to‐face, train‐the‐trainer day, then led 14 one‐hour educational sessions to 279 district dietitians tailored to local situations, facilities and resources. NCP/IDNT were embedded into local processes and chart audits completed. Pre‐/post‐implementation surveys were completed by 86 dietitians. Results Pre‐implementation results showed positive attitudes regarding the value of NCP/IDNT (mean 1.89, SD 0.67, 1 = strongly agree, 5 = strongly disagree). Dietitians identified management support; practice, tutorials and workshops; mentor support; and follow up audits as important for successful implementation. Most attendees (81%) completed ≥10/13 tutorials and 86% (415/480) of audited charts included Nutritional Diagnosis statements. Post‐implementation familiarity, confidence and knowledge of NCPT (Nutrition Care Process Terminology) significantly improved (P < 0.001). Conclusions Prior to implementation, respondents viewed the NCP/IDNT as applicable to their practice areas. The train‐the‐trainer program with frequent teleconference and email support was effective in improving knowledge, confidence, preparedness for implementing NCPT and charting behaviour. Although training was positively received and has achieved good results, dietitians identified the need for ongoing training and support to further increase confidence following implementation.